2021
DOI: 10.1037/pag0000596
|View full text |Cite
|
Sign up to set email alerts
|

State mindfulness and affective well-being in the daily lives of middle-aged and older adults.

Abstract: Contemporary conceptualizations of mindfulness refer to paying attention to the present moment with an open and nonjudgmental attitude. Empirical research is increasingly focusing on mindfulness as a dynamic and multifaceted state that can fluctuate across situations and time. The present study aimed to extend existing knowledge by using experience-sampling methodology to examine state-level mindfulness, pleasant/unpleasant event occurrence, and affective well-being in the everyday lives of middle-aged and old… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 89 publications
2
10
0
Order By: Relevance
“…This finding is consistent with many research findings conducted both in our country (i.e. Turkey) and in other countries and is one of the most well-known findings of the SST in the literature (Lang and Carstensen, 2002;Mahlo and Windsor, 2021;Soylu and Ozekes, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…This finding is consistent with many research findings conducted both in our country (i.e. Turkey) and in other countries and is one of the most well-known findings of the SST in the literature (Lang and Carstensen, 2002;Mahlo and Windsor, 2021;Soylu and Ozekes, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…Thus, older adults may be better at emotion regulation because they are willing to accept short-term discomfort for longer term well-being (although this might speak against SST’s present-oriented focus). A recent experience-sampling study of state mindfulness found that the mindfulness facet of nonjudgmental acceptance predicted more momentary positive affect and less momentary negative affect and less reactivity to hassles, especially among relatively older participants (Mahlo & Windsor, 2021). The complex interface of possible reduced reactivity and enhanced acceptance with age warrants further study: It may be that older adults are better at using acceptance to modulate their responses, or they may have lessened responses and thus infer that they must be accepting them.…”
Section: What Else Could Underlie Older Adults’ Positive Affective Ex...mentioning
confidence: 99%
“…For 10 consecutive days, participants received a link to the evening survey at approximately 8:00 p.m., which was available for 3 h. The survey measured daily stressors, AARC, vitality and affect. Participants also received survey links at randomly spaced intervals four times per day as part of a larger study [see (44)], however, the variables reported here were only assessed in the evening surveys. A response-based compensation approach was offered as follows: Participants received $10 AUD as base compensation, with tiered incentives offered for greater completion of daily surveys (over 60% = an additional $25, over 80% = an additional $40).…”
Section: Participants and Proceduresmentioning
confidence: 99%